Katalis (NaOH) Proses Pengelolaan Limbah Zat Emulsifier - Rinda Nainggolan; Puspanitresna Puspanitresna; Delia Silvi A; Pingkan Adinda R. P; Ganjar Eko P (Universitas Maritim AMNI Semarang, 2024)
Emulsifier is one of the oleochemical products with high economic value. An alternative material that can be used as an emulsifier is pliek oil. The catalyst that can be used in the emulsifier production process is NaOH. The addition of this catalyst can enhance the glycerol's ability in oil to break down fatty acids, accelerate reactions, and suppress the reformation of diglycerides, which are then converted into monoglycerides through the more active glycerol and NaOH. This research aims to analyze the functional groups of the emulsifier substance, the influence of time and the amount of NaOH catalyst, and the characteristics of the emulsifier substance obtained from pliek oil with NaOH catalyst using the glycerolysis process. The research results show that in the FT-IR test, there is a peak at the wavenumber of 3741 cm-1, indicating the presence of the O-H group. The absorption peak at the wavenumber of 1506 cm-1 is characterized as the stretching vibration of C-C. At the wavenumber of 1273 cm-1, there is the presence of the C-N group. The influence of time and NaOH catalyst on the emulsifier substance, with the highest values based on the yield test, is obtained at a reaction time of 1 hour with a 4% catalyst, yielding 93.73%; the saponification value, with the highest value obtained at a reaction time of 2.5 hours with a 4% catalyst, is 161.41; the best acid value is obtained at a reaction time of 2.5 hours with an 8% catalyst, amounting to 0.35.